Distinct roles of two conserved Staufen domains in oskar mRNA localization and translation. - Micklem, D.R.; Adams, J.; Grunert, S.; St. Johnston, D. (The EMBO Journal, 2000)
Drosophila Staufen protein is required for the localization of oskar mRNA to the posterior of the oocyte, the anterior anchoring of bicoid mRNA and the basal localization of prospero mRNA in dividing neuroblasts. The only regions of Staufen that have been conserved throughout animal evolution are five double-stranded (ds)RNA-binding domains (dsRBDs) and a short region within an insertion that splits dsRBD2 into two halves. dsRBDs 1, 3 and 4 bind dsRNA in vitro, but dsRBDs 2 and 5 do not, although dsRBD2 does bind dsRNA when the insertion is removed. Full-length Staufen protein lacking this insertion is able to associate with oskar mRNA and activate its translation, but fails to localize the RNA to the posterior. In contrast, Staufen lacking dsRBD5 localizes oskar mRNA normally, but does not activate its translation. Thus, dsRBD2 is required for the microtubule-dependent localization of osk mRNA, and dsRBD5 for the derepression of oskar mRNA translation, once localized. Since dsRBD5 has been shown to direct the actin-dependent localization of prospero mRNA, distinct domains of Staufen mediate microtubule- and actin-based mRNA transport.